Stretch goals and the distribution of organizational performance - Gary, M.; Yang, Miles; Yetton, P.; Sterman, J. (2017)
Many academics, consultants, and managers advocate stretch goals to attain superior organizational performance. However, existing theory speculates that, although stretch goals may benefit some organizations, they are not a “rule for riches” for all organizations. To address this speculation, we use two experimental studies to explore the effects on the mean, median, variance, and skewness of performance of stretch compared with moderate goals. Participants were assigned moderate or stretch goals to manage a widely used business simulation. Compared with moderate goals, stretch goals improve performance for a few participants, but many abandon the stretch goals in favor of lower self-set goals, or adopt a survival goal when faced with the threat of bankruptcy. Consequently, stretch goals generate higher performance variance across organizations and a right-skewed performance distribution. Contrary to conventional wisdom, we find no positive stretch goal main effect on performance. Instead, stretch goals compared with moderate goals generate large attainment discrepancies that increase willingness to take risks, undermine goal commitment, and generate lower risk-adjusted performance. The results provide a richer theoretical and empirical appreciation of how stretch goals influence performance.